Evaluation of noninvasive specimens to diagnose livestock exposure to toxic larkspur (Delphinium spp.). (1st April 2019) - Stonecipher, Clinton A.; Lee, Stephen T.; Green, Benedict T.; Cook, Daniel; Welch, Kevin D.; Pfister, James A.; Gardner, Dale R.
Abstract: Larkspurs ( Delphinium spp.) are native perennial plants that have a serious toxic potential to cattle on foothill and mountain rangelands in the western United States. Livestock death due to larkspur toxicity is attributed to norditerpenoid alkaloids. Diagnosing plant poisonings in livestock is often challenging. The objective of this study was to evaluate the use of three matrices; earwax, oral fluid, and nasal mucus, as noninvasive specimens to determine livestock exposure to larkspurs. Reversed phase high performance liquid chromatography – high resolution mass spectrometry was used to analyze for norditerpene alkaloids, in all three matrices, in cattle administered a single dose of larkspur. Earwax, oral fluid, and nasal mucus were collected over 6 days post-dosing. Methyllycaconitine (MLA) and deltaline concentrations in earwax ranged from 0.4 ± 0.1 to 0.2 ± 0.06 and 0.6 ± 0.5 to 0.11 ± 0.08 ng/mg, respectively. MLA and deltaline concentrations in oral fluid ranged from 0.08 ± 0.03 to 0.01 ± 0.002 ng/mg and 0.07 ± 0.03 ng/mg to not detected (ND), respectively. MLA and deltaline concentrations in nasal mucus ranged from 0.2 ± 0.13 to 0.03 ± 0.01 ng/mg and 0.2 ± 0.12 ng/mg to ND, respectively. The ability to detect differing norditerpene alkaloid chemotypes from two different Delphinium spp. was also possible in the three matrices. This study demonstrates the potential of earwax, oral fluid, and nasal mucus as noninvasive specimens for chemical analyses to aid in the diagnosis of livestock that may have been exposed to and poisoned by larkspur plants. Highlights: Diagnosing plant poisonings in livestock is often challenging. Earwax, oral fluid, and nasal mucus can aid in the diagnosis of livestock exposure to plant toxins. Alkaloid profiles from larkspur consisting of diverse chemotypes were differentiated in earwax, oral fluid, and nasal mucus. Earwax, oral fluid, and nasal mucus can be used for analyses to aid in the diagnosis of livestock exposure to larkspur.